2013
DOI: 10.1161/strokeaha.113.001612
|View full text |Cite
|
Sign up to set email alerts
|

123 I-Iomazenil Single Photon Emission Computed Tomography Visualizes Recovery of Neuronal Integrity by Bone Marrow Stromal Cell Therapy in Rat Infarct Brain

Abstract: Background and Purpose-This study was aimed to assess whether 123 I-iomazenil (IMZ) single photon emission computed tomography can serially monitor the effects of bone marrow stromal cell (BMSC) transplantation on neuronal integrity in infarct brain of rats. Methods-The BMSCs were harvested from green fluorescent protein-transgenic rats and were cultured. The rats were subjected to permanent middle cerebral artery occlusion. Their motor function was serially quantified throughout the experiments. The BMSCs or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…These cells also have the capability to differentiate into GABAergic neuron-like cells when genetically engineered or treated with a cocktail conditioned medium [7, 10, 11]. Furthermore, previous studies have shown that GABAergic neuron-like cells derived from BMSCs express GABA and GABA A receptors following transplantation into the brain in a cerebral infarct model [16, 17]. These results have supported BMSCs as a potential source of GABA-synthesizing cells for grafting in neurological disorders.…”
mentioning
confidence: 93%
“…These cells also have the capability to differentiate into GABAergic neuron-like cells when genetically engineered or treated with a cocktail conditioned medium [7, 10, 11]. Furthermore, previous studies have shown that GABAergic neuron-like cells derived from BMSCs express GABA and GABA A receptors following transplantation into the brain in a cerebral infarct model [16, 17]. These results have supported BMSCs as a potential source of GABA-synthesizing cells for grafting in neurological disorders.…”
mentioning
confidence: 93%
“…Various types of cells, including neural stem cells, embryonic stem cells, mesenchymal stem cells, and adipose stem cells, have been found to improve neurological outcome in animal stroke models [4][5][6][7]. Bone marrow-derived mononuclear cells (MNCs) are composed of diverse cell populations and are attractive as a cell therapy for the acute stage of stroke because they permit rapid bone marrow harvest and separation for autologous transplantation [8].…”
mentioning
confidence: 99%
“…This procedure provides further hypoperfusion in the MCA territory by reducing collateral flow. The high reproducibility of focal cerebral infarction has been verified in this model (Fluri et al, 2015;Saito et al, 2013;Sugiyama et al, 2011).…”
Section: Stroke Model Ratsmentioning
confidence: 62%
“…The model used in the present study is known to produce focal cerebral infarction with high reproducibility (Fluri et al, 2015;Saito et al, 2013;Sugiyama et al, 2011), and is achieved through a combination of persistent antegrade hypoperfusion by direct MCAO and transient retrograde collateral hypoperfusion by bilateral common carotid artery occlusion (CCAO). Since leptomeningeal collateral flow in the rodent brain is well developed, direct MCAO only is not sufficient to ensure the induction of infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation